EFFICIENCY OF ALPHACALCIDOL USAGE FOR CORRECTION OF SECONDARY HYPERPARATHYROIDISM IN PATIENTS WITH CHRONIC KIDNEY DISEASE IN PREDIALISIS PERIOD - Martynyuk, L. P.; Ruzhytska, O. O.; Martynyuk, L. P.; Klym, A. A.; Martynyuk, O. S.; Symko, G. B.; Shevchenko, N. Y. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The aim of the our work was to study the prevalence of secondary hyperparathyroidism (SHPT) in patients with non-dialysis CKD and efficacy of treatment SHPT using low doses of the active metabolite of vitamin D - alphacalcidol. Materials and methods. The study involved 45 patients with non-dialysis CKD. We studied the levels of parathyroid hormone (PTH), total and ionized calcium, and phosphorus in serum, as determined by anthropometric indicators. The results are compared with target levels and depending on the stage of CKD as recommended NKF-K/DOQI 2003. The results of the study. PTH level in the examined patients ranged from 0.3 to 953.8 pg/ml, the average was - (234,49±34,99) pg/ml, the average level of total calcium was (2,08±0,06) mmol/L, ionized calcium - (0,74±0,07) mmol / l, phosphorus - (1,62± 0,11) mmol/ l. The analysis of calcium-phosphorus homeostasis before and after treatment with the main group of patients under the influence of treatment alphacalcidol showed significant increase of ionized calcium and PTH levels decrease by 51%. Conclusions. It is ascertained that secondary hyperparathyroidism occurs in about 65% cases among patients with chronic kidney disease in predialisis period. The efficiency of low doses of alphacalcidol in comparison with standard therapy of calcium carbonate in the generally accepted doses in treatment of secondary hyperparathyroidism was found. The positive dynamics of clinical and biochemical manifestations of hyperparathyroidism influenced by treatment with low doses of alphacalcidol were developed.